Snow Pads Used for Pipeline Construction in Alaska, 1976. Construction, Use and Breakup - Johnson,Philip R; Collins,Charles M (1980)
Construction pads made of snow were used to build two sections of the Trans Alaska Pipeline and a small gas pipeline during the winter of 1975-76. Construction during the winter has become increasingly common in the Arctic. Surface travel and the use of heavy construction equipment on the unprotected tundra have been severely restricted, even during the winter, so the use of temporary winter roads and construction pads built of snow and ice has been advocated and is being adopted. The three snow construction pads mentioned above were the first snow roads and construction pads used on a large scale in Alaska. Snow roads and construction pads have two objectives: to protect the underlying vegetation and upper layers of the ground, and to provide a hard, smooth surface for travel and the operation of equipment. Several types have been built, and a brief discussion is given of their history and classification systems. The three snow construction pads used in construction of the Trans-Alaska Pipeline and the small gas pipeline in 1975-76 were visited and observed while in use. (Author)